Rethinking Poverty - Knight, Barry (Policy Press, 2017)
Epdf available Open Access under CC-BY-NC licence. There is a demand for a new narrative to enable us to escape from the crisis in our society. This book argues that we need to start with the society we want, rather than framing poverty as a problem to be solved. It calls for a bold forward-looking social policy that addresses continuing austerity, under-resourced organisations and a lack of social solidarity. Based on a research programme carried out by the Webb Memorial Trust involving leading organisations, academics, community activists, children, and surveys of more than 12,000 people living in poverty, a key theme is power which shows that the way forward is to increase people's sense of agency in building the society that they want.